Physiotherapists' approaches to patients' concerns in back pain consultations following a psychologically informed training program - Cowell,I; McGregor,A; O'Sullivan,P; O'Sullivan,K; Poyton,R; Schoeb,V; Murtagh,G (Qualitative Health Research, 2021)
Guidelines advocate a combined physical and psychological approach to managing non-specific chronic low back pain (NSCLBP), referred to as psychologically informed practice (PIP). PIP is underpinned by patient-centered principles and skilled communication. Evidence suggests that a physiotherapist-focused style of communication prevails in physiotherapy. There is a recognized need for observational research to identify specific communication practices in physiotherapy interactions. This observational study explored the interactional negotiation of agenda setting following a PIP training intervention, by identifying and describing how physiotherapists solicit and respond to the agenda of concerns that patients with NSCLBP bring to primary care initial encounters. The research setting was primary care. Nineteen initial physiotherapy consultations were video-recorded, transcribed, and analyzed using conversation analysis, a qualitative observational method. These data revealed a patient-focused style of communication where trained physiotherapists demonstrated a collaborative and responsive style of verbal and nonverbal communication to solicit, explore, and validate patients’ concerns.